The Increase in CD14+CD16+ Monocytes is Correlated with Cardiovascular Disease Risk Marker in Type 2 Diabetes - Hikmat, Ujang Saeful; Prijanti, Ani Retno; Wibowo, Heri; Sukmawati, Indriyanti Rafi; Tahapary, Dicky Levenus (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Type 2 Diabetes (T2D) impairs the innate immune system including monocytes. Monocytes are divided into two subgroups depending on the expression of cluster of differentiation (CD)14 and CD16 receptors, namely CD14+CD16- and CD14+CD16+. CD14+CD16+ are proinflammatory monocytes and develop into M1 type macrophages, which contribute to foam cell production, a risk factor for cardiovascular disease (CVD). Therefore, it is important to determine the influence of T2D conditions on changes in monocyte subsets and whether these changes correlate with CVD risk markers.METHODS: Peripheral blood mononuclear cell (PBMC) was obtained from 10 T2D subjects and 10 healthy donors. Subsequently, PBMC was incubated for 24 hours with and without 10 mL lipopolysaccharide. Flow cytometry was used to evaluate CD14 and CD16 expression, while multiplex immunoassays were applied to measure interleukin (IL)-1b and IL-10 concentrations in supernatants.RESULTS: In T2D, the percentage of CD14+CD16+ monocytes increased (p=0.07), and an increase in CD14+CD16+ monocytes more than 6.8% was linked with CVD risk markers (r=10.146, p=0.002). Meanwhile, inflammatory mediators released by monocytes shown an increase in IL-1b (p=0.041) but not in IL-10 (p=0.082) in T2D subjects. Fasting blood glucose levels were also found to be substantially linked with an increase in CD14+CD16+ monocytes (r=0.530, p=0.016).CONCLUSION: T2D patients had a higher percentage of CD14+CD16+ monocytes and IL-1b levels than healthy donors. An increase in CD14+CD16+ monocytes above 6.8% associated with CVD risk markers in T2D patients.KEYWORDS: type 2 diabetes, monocytes, CD14, CD16, cardiovaskular disease risk marker